Acute Suppurative Otitis Media With Spontaneous Tympanic Membrane Perforation in a School-Aged Child : A Comprehensive Family Medicine Case Report - Dasa Novita, Khuznita; Barasabha, Thareq; Ogan, Muhammad (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2025)
Background: Acute otitis media (AOM) is one of the most frequent infections in children and may progress to acute suppurative otitis media (ASOM) with tympanic membrane perforation when treatment is delayed. This report presents a holistic, family medicine–based assessment and management of a pediatric patient with ASOM complicated by spontaneous perforation, triggered by an antecedent upper respiratory tract infection. Case Presentation: An 8-year-old girl presented with acute left ear pain, irritability, reduced hearing, fever, and subsequently otorrhea occurring one day after symptom onset. The episode followed a week-long history of cough, rhinorrhea, and nasal obstruction. Examination revealed left-sided mucopurulent otorrhea, loss of light reflex, and clinical features consistent with ASOM in the perforation stage. Family, environmental, and behavioral factors, including cold exposure, crowded sleeping arrangements, and delayed healthcare seeking, contributed to disease progression. Treatment included amoxicillin, analgesics, antihistamines, an expectorant, and ear care education, accompanied by structured family-centered and community-oriented interventions. Rapid improvement was observed within three days. Conclusion: This case highlights the importance of early recognition of upper respiratory infections, timely management, and a comprehensive family medicine approach to prevent complications of ASOM in children.